Causes of ocular surface tissue lesions in patients with pseudoexfoliation syndrome - V. V. Potemkin; E. V. Ageeva (Российский офтальмологический журнал)
Pseudoexfoliation syndrome (PEX) is a widespread generalized disease. While changes of diverse structures of the eyeball in PEX are studied in detail, the situation is different with the state of ocular surface tissues. Purpose:to detect possible causes of damage of ocular surface tissues in patients with PEX. Material and methods. 130 patients (260 eyes) were divided into two groups: the main group of 66 patients (132 eyes) aged 75.95 ± 1.62 years with PEX syndrome and the control group of 64 patients (128 eyes)aged 73.78 ± 2.12 years without PEX. We evaluated the condition of meibomian glands, the tone of lower eyelids, tear film break-up time, the staining grade of conjunctiva and cornea and the extent of conjunctivochalasis, conducting Schirmer’s test-II. Results.Meibomian gland dysfunction was significantly more expressed in patients with PEX. Signs of atonic changes of lower lids were found to be more common in patients with PEX. PEX also showed a statistically significant reduction of tear film break-up time and a pronounced damage of conjunctival surface. Conclusion. PEX is not only accompanied by damaged tissues of the ocular surface but also by damaged adnexa and eye lide edges. The obtained data reveal a kind of vicious cycle consisting of meibomian gland dysfunction, atonic lower eyelid malposition, and damaged tissues of the ocular surface. For citations: Potemkin V.V., Ageeva E.V. Causes of ocular surface tissue lesions in patients with pseudoexfoliation syndrome. Russian ophthalmological journal. 2017; 10 (3): 62-68. doi: 10.21516/2072-0076-2017-10-3-62-68 (in Russian).